Acetic acid positively modulates proline metabolism for mitigating PEG-mediated drought stress in Maize and Arabidopsis - Mahmud, Sakil; Kamruzzaman, Mohammad; Bhattacharyya, Sabarna; Alharbi, Khadiga; Abd El Moneim, Diaa; Mostofa, Mohammad Golam (Frontiers in Plant Science, 2023)
Osmotic imbalance is one of the major consequences of drought stress, negatively affecting plant growth and productivity. Acetic acid has modulatory roles in osmotic balance in plants; however, the mechanistic insights into acetic acid-mediated osmotic adjustment under drought stress remains largely unknown. Here, we investigated how seed priming and seedling treatment with acetic acid enabled maize plants overcoming polyethylene glycol (PEG)-induced drought effects. Maize seeds primed with acetic acid showed better growth performance when compared with unprimed seeds under PEG application. This growth performance attributed to improved growth traits, such as fresh weight, dry weight, length of shoots and roots, and several leaf spectral indices, including normalized difference vegetation index (NDVI) and chlorophyll absorption in reflectance index (MCARI). The levels of oxidative stress indicators hydrogen peroxide (H2O2) and malondialdehyde (MDA) did not alter significantly among the treatments, but proline content was significantly elevated in plants receiving acetic acid under PEG-treatments. Seedlings treated with acetic acid also led to a significant recovery of maize plants from drought-induced wilting. Although growth traits remained unchanged among the treatments, the enhancement of leaf water content, photosynthetic rate, proline level, and antioxidant enzyme activities along with reduced level of H2O2 and MDA in acetic acid-supplemented drought plants indicated a positive regulatory role of acetic acid in maize tolerance to drought. The high expression of Δ1-pyrroline-5-carboxylate synthetase 1 (P5CS1) and the subsequent elevation of proline level upon acetic acid application were further validated using wild type and proline biosynthetic mutant p5cs1 of Arabidopsis. Results showed that acetic acid application enabled wild type plants maintain better phenotypic appearance and recovery from drought stress than p5cs1 plants, suggesting a crosstalk between acetic acid and proline metabolism in plants under drought stress. Our results highlight the likely role of acetic acid in proline accumulation for conferring plant tolerance to drought stress.